Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Aksesoris HP Di Shopee Mahasiswa Unwaha - Purbowo, Purbowo; Maarif, Muhammad Salafudin (Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to identify the factors that influence the decision to purchase HP accessories on Shopee using a case study of Unwaha Jombang students. This study uses five independent variables, namely motivation, perception, knowledge, culture, and satisfaction. Data were collected from 100 respondents through an online questionnaire and analyzed using multiple linear regression. The results show that culture and satisfaction have a significant positive effect on the decision to purchase HP accessories on Shopee. However, motivation, perception, and knowledge do not have a significant effect on the decision to purchase HP accessories on Shopee. These findings can help HP accessory sellers on Shopee understand the factors that can influence customer purchasing decisions, especially among Unwaha Jombang students